Strategic Partnership between SME Retailers and Modern Suppliers in Indonesia: A Relationship Marketing Approach - Setyawan, Anton; Mudhofar, Fairuz; Arum, Yasinta; Susila, Ihwan; Nasir, Moechammad (Organizations and Markets in Emerging Economies, 2022)
This study aimed to analyze the business marketing relationship between modern suppliers and SME retailers to empower and strengthen SMEs in Indonesia. The theoretical framework is the relationship marketing model developed by Morgan and Hunt (1994). This framework is based on trust and commitment as the two key mediating variables. The study surveyed 250 SME retailers as respondents selected using purposive sampling. Furthermore, hypotheses were tested using path analysis. The findings showed that trust and commitment to business partnerships mediate the effect of influence strategy on loyalty to business partners and economic performance. The influence strategy significantly affects the business performance of the involved parties. Therefore, strategic business partnerships with modern suppliers improve SME retailers’ business performance.